Development of a Pseudomonas syringae–Arabidopsis Suspension Cell Infection System for Investigating Host Metabolite-Dependent Regulation of Type III Secretion and Pattern-Triggered Immunity - Qing Yan; Conner J. Rogan; Jeffrey C. Anderson (Molecular Plant-Microbe Interactions, 2019)
The importance of pattern-triggered immunity (PTI) in plant defense has been clearly established through genetic studies of mutants lacking functional pattern recognition receptors (PRRs) and signaling components downstream of PRR activation. Despite extensive knowledge of PRR-mediated signaling responses to pathogen-associated molecular patterns (PAMPs), little is known about which of these responses, if any, are directly responsible for limiting bacterial growth. In this work, we established a protocol for coculturing the bacterial pathogen Pseudomonas syringae pv. tomato DC3000 and Arabidopsis suspension cells. The system closely mirrors infection processes that occur in leaves, with bacteria relying on the type III secretion system (T3SS) for maximal growth and PAMP-induced plant defenses effectively limiting bacterial growth. To demonstrate the utility of this system, we investigated the molecular basis of PAMP-induced growth inhibition and discovered that T3SS-associated genes are inhibited when DC3000 is cocultured with PAMP-treated plant suspension cells. To determine the underlying mechanism of decreased T3SS gene expression, we performed metabolomics and biochemical analyses of suspension cell exudates and identified 14 metabolites that significantly increased or decreased following PAMP treatment. Citric acid, a known inducer of T3SS gene expression in DC3000, was among several organic acids decreased in exudates from PAMP-treated plant cells. Exogenous addition of citric acid increased T3SS gene expression and partially recovered growth of DC3000 in the presence of PAMP-treated cells, indicating that a portion of PAMP-induced defense in this system is decreased extracellular release of this metabolite. We envision that the well-defined infection conditions of this coculture system will be valuable for quantitative studies of type III effector delivery by P. syringae. Furthermore, this system provides a unique ‘top-down’ approach to unravel the molecular basis of PTI against P. syringae.